Bioremediation of Dyes in Textile Effluents by Aspergillus oryzae - Corso, Carlos Renato [UNESP]; Maganha de Almeida, Ana Carolina [UNESP] (Springer, 2009)
In this study Aspergillus oryzae was utilized to remove azo dyes from aqueous solution. Physically induced in its paramorphogenic form to produce standardized mycelial pellets, the non-autoclaved and autoclaved hyphae biomass was applied to biosorb the reactive dyes Procion Red HE7B (PR-HE7B) and Procion Violet H3R (PV-H3R) at different pH values (2.50, 4.50, and 6.50). The best pH for biosorption was 2.50, though the autoclaved demonstrated a higher biosorption capacity than the non-autoclaved pellets. The toxicity level was determined using the Trimmed Spearman-Karber method with Daphnia similis in all bioassays. The calculated toxicity of PV-H3R (LC(100) 62.50 mu g mL(-1)) was higher than to PR-HE7B (LC(100) 300.00 mu g mL(-1)), and its results brought out that the decrease of toxicity levels to zero might be accomplished by adding small quantities of pelletized A. oryzae to the solutions.